إدارة الأزمات الاقتصادية: مقارنة بين أزمة الكساد 1929، والأزمة المالية 2008 - بن خيرة, الطاهر (جامعة الوادي - University of Eloued, 2022)
الأزمات الاقتصادية جزء من النظام الرأسمالي، وسمة من سماته الملازمة له، وقد زادت تأثير هذه الأزمات منذ نشوء الأسواق المالية مرور بأصعب أزمة 1929 إلى الأزمة المالية العالمية 2008. ونهدف من خلال هذه البحث التعرف على أوجه الشبه والاختلاف بين الازمة الاقتصادية 1929، والازمة المالية 2008، من خلال أسبابها وتداعياتها وتأثيرها على الأنظمة الاقتصادية العالمية، وإبراز كيفية إدارة هذه الأزمات وآليات معالجتها وما مدى جدواها، ومن اهم النتائج المتوصل اليها انه برغم كل الجهود والحلول فان آثار الازمتين مازالت تلقي بظلالها ونتائجها السلبية على الاقتصاد العالمي ولذلك من الضروري البحث عن بدائل أخرى لإدارة الأزمات الاقتصادية والتي نراها في التمويل والصيرفة الإسلامية كبديل. Economic crises are part of the capitalist system, and an inherent feature of it, and the impact of these crises has increased since the emergence of financial markets through the most difficult crisis of 1929 to the global financial crisis of 2008. We aim through this research to identify the similarities and differences between the economic crisis of 1929 and the financial crisis of 2008, through its causes, repercussions, and its impact on global economic systems, and to highlight how these crises are managed and the mechanisms for addressing them and the extent of their feasibility, and one of the most important results reached is that despite all efforts and solutions The effects of the two crises still cast shadows and negative consequences on the global economy, and therefore it is necessary to search for other alternatives to manage economic crises, which we see in Islamic finance and banking as an alternative.
دراسة تاريخية اقتصادية
مقال
Keywords: الازمة الاقتصادية ; الازمة المالية ; إدارة الازمات ; المالية الاسلامية; Economic crisis; Financial crisis; Crisis management; Islamic finance